The International Relations of the Dead: Transboundary Ancestral Claims and Regional Conflict in West Africa - OWA, Owa Egbara (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The prevailing Westphalian paradigm in International Relations (IR), which centers on the sovereign, territorial state as the primary actor, proves inadequate for diagnosing and resolving a distinct class of protracted conflicts in post-colonial Africa. This article posits that conflicts fueled by transboundary ancestral claims—assertions of rights and belonging based on kinship groups' sacred connections to burial grounds, shrines, and historical territories straddling modern borders—constitute a unique category of ontological security dilemma. We introduce the concept of “Ancestral Sovereignty” to theorize the spiritual and cultural authority that emanates from these connections, challenging the monopoly of the modern state. This framework moves beyond the materialist and secular biases of mainstream IR theories by arguing that the veneration of ancestors and the custodianship of their resting places generate a potent, non-state form of political agency. Through a comparative case study analysis of the adjudicated but unresolved Nigeria-Cameroon dispute over the Bakassi Peninsula and the latent tensions of the partitioned Ewe nation across the Ghana-Togo border, this paper demonstrates how ancestral attachments foster resistance to international legal rulings and sustain irredentist sentiments. The analysis reveals that the intractability of these disputes stems from a fundamental clash between the state's cartographic rationality and the community's sacred geography, a clash that regional bodies like the Economic Community of West African States (ECOWAS) are institutionally ill-equipped to manage. The paper concludes by proposing a substantive recalibration of regional conflict resolution mechanisms, advocating for the formal integration of traditional governance structures and the adoption of an ontological security lens to forge a more culturally-grounded and sustainable peace in regions where the dead remain constitutive agents in the political realm.